2022
DOI: 10.3390/ijerph191610057
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Peripheral Arterial Occlusive Disease with Periodontitis and Dental Scaling: A Nationwide Population-Based Cohort Study

Abstract: Periodontitis (PD) is a common oral disease associated with various other diseases, particularly those affecting the cardiovascular system. This study explored whether peripheral artery occlusive disease (PAOD) is associated with PD and dental scaling. This study was a retrospective cohort study design from 2000 to 2018. The study population was newly diagnosed with periodontitis. The comparison group was defined as never diagnosed with periodontitis. The outcome variable was defined with the diagnosis of peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Interestingly, another recent powerful population-based cohort study showed that the risk for peripheral artery occlusive disease, a condition with similar atherosclerosis pathogenesis, was increased in patients that had periodontal disease. This same study also found that patients undergoing at least one dental scaling procedure, a treatment for periodontal disease, had lower risk of peripheral artery occlusive disease ( Yeh et al, 2022 ).…”
Section: Studies On the Link Between Oral Health And Atherosclerosismentioning
confidence: 73%
“…Interestingly, another recent powerful population-based cohort study showed that the risk for peripheral artery occlusive disease, a condition with similar atherosclerosis pathogenesis, was increased in patients that had periodontal disease. This same study also found that patients undergoing at least one dental scaling procedure, a treatment for periodontal disease, had lower risk of peripheral artery occlusive disease ( Yeh et al, 2022 ).…”
Section: Studies On the Link Between Oral Health And Atherosclerosismentioning
confidence: 73%
“…Because it causes chronic ischaemia, ASO, which is defined by atherosclerotic plaque accumulation that results in arterial stenosis and occlusion, is extremely common and poses a major risk to limb viability 3 . The pathophysiology of atherosclerosis, which underpins not just ASO but also coronary artery disease and hypertension, has been linked to the adoption of lifestyles burdened with excessive intakes of salt, sugar and fat in addition to smoking habits 4,5 …”
Section: Introductionmentioning
confidence: 99%
“…3 The pathophysiology of atherosclerosis, which underpins not just ASO but also coronary artery disease and hypertension, has been linked to the adoption of lifestyles burdened with excessive intakes of salt, sugar and fat in addition to smoking habits. 4,5 When ASO first appears, it may just be weariness. However, it can quickly advance to critical limb ischaemia, which is indicated by skin pallor, thicker nails and pain at rest.…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral artery occlusion disease (PAOD), also known as peripheral artery disease (PAD), is a manifestation of atherosclerosis that causes the narrowing or occlusion of the arterial lumen. Blood flow and perfusion are impaired in the area of the distal part of the affected arteries [ 1 ]. Figures on the prevalence of PAOD vary with diagnostic criteria and the study population.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms of PAOD in the male population were reported to be more severe than in the female population [ 6 ]. The diagnosis of PAD was also presented in the previous study [ 1 ].…”
Section: Introductionmentioning
confidence: 99%